Unveiling host-genetic drivers of caecal microbial communities in chickens through genome-wide association studies - Hinsu, Ankit; Dai, Xiaoxia; Dadousis, Christos; Hay, Melanie; Fosso, Bruno; Crotta, Matteo; Pandit, Ramesh; Guitian, Javier; Tomley, Fiona; Koringa, Prakash; Joshi, Chaitanya; Blake, Damer; et al. (Frontiers in Microbiomes, 2025)
Enteric microbiota plays a crucial role in the health and productivity of poultry, including influences on nutrient absorption, immune function, and pathogen resistance. In this study, we conducted a genome-wide association study (GWAS) to identify host genetic variants associated with selected bacterial genera found in chickens. We used high-density 600K SNP Affymetrix DNA arrays for genotyping, alongside 16S rRNA gene sequencing to profile caecal microbiota from the same individual chickens. A commercial broiler line (Cobb400, n = 300) and an indigenous (Kadaknath, n = 300) chicken breed from India were investigated, allowing for a comprehensive cross-ecotype analysis. Our analysis identified several host-genetic markers and candidate genes associated with the presence and abundance of specific bacterial genera with known pathogenic or commensal roles, and with specific caecal Enterotypes. Whole-genome sequencing data were then used to further investigate candidate regions around significantly associated variants from the high-density DNA array. Of note, we found markers nearby the genes coding for classical complement activation component C1q, ephrin receptors, and other immunity and inflammatory responses as well as genes coding for products associated with vitamin and co-factor metabolism. The results underscore the impact that host genetics has on the regulation of the gut microbiota and highlights potential pathways through which host genetic variation influences host-bacterial crosstalk and potentially modulates microbial community structure. These findings contribute to the growing understanding of the genetic basis of host-microbiota interactions and offer new avenues for improving poultry health and productivity through selective breeding strategies targeting the microbiome.